2022
DOI: 10.3390/su14063229
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Nomophobia, Stress, and Loneliness on Smartphone Addiction among Young Adults during and after the COVID-19 Pandemic: An Israeli Case Analysis

Moti Zwilling

Abstract: Technological development in recent times has dramatically changed the way people live, interact with, and consume information. Since the emergence of the first iPhone in January 2007 until today, mobile phones are used daily for a range of purposes. Using mobile phones for various purposes intensified during the COVID-19 pandemic due to isolation or government lockdown regulations. However, along with the advantages of smartphone usage there are many disadvantages such as smartphone addiction and continuous e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 59 publications
0
18
1
5
Order By: Relevance
“…Hence the second hypothesis was rejected. Our finding was in contrast with previous studies which found that social support was negatively associated with nomophobia (Shirani, 2017 ; Zhou et al, 2021 ; Zwilling, 2022 ). During the COVID-19 pandemic lockdown, non-face-to-face contact through social media use was one of the methods to increase social support (Chen et al, 2021 ; Zhang et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Hence the second hypothesis was rejected. Our finding was in contrast with previous studies which found that social support was negatively associated with nomophobia (Shirani, 2017 ; Zhou et al, 2021 ; Zwilling, 2022 ). During the COVID-19 pandemic lockdown, non-face-to-face contact through social media use was one of the methods to increase social support (Chen et al, 2021 ; Zhang et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 99%
“…The loneliness of remaining at home during the COVID-19 epidemic may have prompted teens to utilize mobile phones for amusement in order to alleviate the psychological feeling of isolation ( 118 , 119 ). Both social loneliness (lack of intimate connections with others) ( 120 ) and emotional loneliness (which originates from not frequenting social circles) can generate unpleasant feelings toward oneself, such as despair and melancholy, which may cause people to overuse cell phones as a method of building relationships, satisfying the desire to belong, and mitigating negative feelings that arise from difficult circumstances ( 121 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have been conducted during the global health crisis on nomophobia: For instance, Bhatnagar et al (2021) assessed nomophobia prior to and during the COVID-19 lockdown, reporting an increase of smartphone overuse during the pandemic restrictions, with a significant proportion of participants with moderate to severe nomophobic symptoms, whereas Sui et al (2022) indicated that nomophobic symptoms tend to be stable when compared with pre-pandemic data; also, Zwilling (2022) showed that nomophobic levels, along with their repercussions on problematic smartphone use, increased from the beginning of the first COVID-19 wave (T1) to the end of the COVID-19 lockdown (T2), highlighting how the addictive outcomes endure longer, even when the pandemic was less widespread; further, Nguyen et al (2022) investigated the effects of nomophobia on stress, also testing the indirect path through loneliness, indicating that the perception of feeling lonely may increase stress in individuals who show nomophobic symptoms.…”
Section: Nomophobia During the Pandemicmentioning
confidence: 99%